Public health economic modelling in evaluations of salt and/or alcohol policies: a systematic scoping review - Joseph Prince Mensah; Chloe Thomas; Robert Akparibo; Alan Brennan (BMC Public Health)
Abstract Background Public health economic modelling is an approach capable of managing the intricacies involved in evaluating interventions without direct observational evidence. It is used to estimate potential long-term health benefits and cost outcomes. The aim of this review was to determine the scope of health economic models in the evaluation of salt and/or alcohol interventions globally, to provide an overview of the literature and the modelling methods and structures used. Methods Searches were conducted in Medline, Embase, and EconLit, and complemented with citation searching of key reviews. The searches were conducted between 13/11/2022 and 8/11/2023, with no limits to publication date. We applied a health economic search filter to select model-based economic evaluations of public health policies and interventions related to alcohol consumption, dietary salt intake, or both. Data on the study characteristics, modelling approaches, and the interventions were extracted and synthesised. Results The search identified 1,958 articles, 82 of which were included. These included comparative risk assessments (29%), multistate lifetables (27%), Markov cohort (22%), microsimulation (13%), and other (9%) modelling methods. The included studies evaluated alcohol and/or salt interventions in a combined total of 64 countries. Policies from the UK (23%) and Australia (18%) were the most frequently evaluated. A total of 58% of the models evaluated salt policies, 38% evaluated alcohol policies, and only three (4% of included modelling studies) evaluated both alcohol- and salt-related policies. The range of diseases modelled covered diabetes and cardiovascular disease-related outcomes, cancers, and alcohol-attributable harm. Systolic blood pressure was a key intermediate risk factor in the excessive salt-to-disease modelling pathway for 40 (83%) of the salt modelling studies. The effects of alcohol consumption on adverse health effects were modelled directly using estimates of the relative risk of alcohol-attributable diseases. Conclusions This scoping review highlights the substantial utilisation of health economic modelling for estimating the health and economic impact of interventions targeting salt or alcohol consumption. The limited use of combined alcohol and salt policy models presents a pressing need for models that could explore their integrated risk factor pathways for cost-effectiveness comparisons between salt and alcohol policies to inform primary prevention policymaking.